Histopathological survey of the mussel Mytilus chilensis (Mytilidae) and the clam Gari solida (Psammobiidae) from southern Chile - Cremonte, Florencia (2015)
A total of 175 specimens of mussels, Mytilus chilensis (Mytilidae), and 56 specimens of clams, Gari solida (Psammobiidae), were collected in natural beds and culture sites of southern Chile. Juvenile mussel specimens (3 cm of maximum length) were free of parasites and diseases, whilst the commercial sized populations was parasitized by intracellular inclusions of bacteria-like organisms in the digestive gland epithelium and in the gills, by ciliates in the gills, turbellarians similar to Paravortex (Rhabocoela) in the intestine lumen and copepods attached to the gills. In addition, the disseminated neoplasia disease was also present although in low prevalences. In the clam, G. solida, prokariotic inclusions were found in the digestive gland epithelium and bacteria-like organisms in the gills, often encapsulated by haemocytes; oocysts containing up to 8 sporozoites similar to Nematopsis (Apicomplexa) in the connective tissue, causing haemocytic infiltration when the intensity of infection was high; ciliates belonging to two different species (one of them similar to Trichodina) inhabiting the gills; and a turbellarian similar to Paravortex in the lumen of digestive system without apparent host reaction. The populations of the bivalve species here studied were devoid of serious pathogens.